PTPN2 targets TAK1 for dephosphorylation to improve cellular senescence and promote adipose tissue browning in T2DM - Liu, Yapeng; Han, Lu; Zhu, Ping; Song, Ming; Zhang, Yaoyuan; Meng, Linlin; Zhang, Wei; Zhang, Cheng; Zhong, Ming (Frontiers in Pharmacology, 2023)
The energy imbalance when energy intake exceeds expenditure acts as an essential factor in the development of insulin resistance (IR). The activity of brown adipose tissue, which is involved in the dissipation of energy via heat expenditure decreases under type 2 diabetic mellitus (T2DM) state when the number of senescent adipocytes increases. However, the underlying molecular mechanism of interaction between adipose tissue browning and senescence as well as IR remains unclear. The protein tyrosine phosphatase non-receptor type 2 (PTPN2) regulates several biological processes by dephosphorylating several cellular substrates; however, whether PTPN2 regulates cellular senescence in adipocytes and the underlying mechanism has not been reported. Therefore, we constructed a model of type 2 diabetic mice with PTPN2 overexpression and revealed that PTPN2 facilitated adipose tissue browning by alleviating senescence, thus improving glucose tolerance and IR in T2DM. Mechanistically, we are the first to report that PTPN2 could bind to transforming growth factor-activated kinase 1 (TAK1) directly for dephosphorylation to inhibit the downstream MAPK/NF-κB pathway in adipocytes and regulate cellular senescence and the browning process subsequently. Our study revealed a critical mechanism of adipocytes browning progression and provided a potential target for the treatment of related diseases.